Associations of neighborhood built, safety, and social environment with walking to and from school among elementary school-aged children in Chiba, Japan - Kimihiro Hino; Erika Ikeda; Saiko Sadahiro; Shigeru Inoue (BMC, 2021)
Abstract Background Although it is globally known that Japan has high prevalence of active school travel among children, there are few international studies on Japanese children's school travel. Moreover, only few studies have focused on the differences in their mode of travel between to-school and from-school. This study examined the associations of neighborhood built, safety, and social environments with walking to/from school among elementary school-aged children in Chiba, Japan. Methods We conducted an online survey with 1545 parents of children aged 6-12 years residing in Chiba between 25 and 27 November 2020 during the COVID-19 pandemic. A neighborhood was defined as the area of a postcode provided by the participants. Each neighborhood environment was assessed based on the built environment (new town designation, walkability, distance to school, population density), social environment (neighborhood cohesion and connection), and safety (CCTVs, a road section for walking alone, safety volunteers). Neighborhood walkability was measured using subscales of the Neighborhood Environment Walkability Scale (youth and abbreviated versions) including crime safety and traffic safety. Parents' perceived influence of COVID-19 on school commuting and after-school activities were also included in the model as covariates. Walking to and from school were separately analyzed using multinomial logistic regressions, where new towns and walkability were computed separately as explanatory variables. Results Four fifths of children walked to and from school daily. Walking to school was positively associated with crime safety, neighborhood connections, and schools sited in new towns. Walking from school had positive associations with traffic safety, neighborhood cohesion, and CCTVs, but negative associations with safety volunteers and after-school activities. The presence of a section for walking alone and perceived influence of COVID-19 had negative associations with walking to and from school. Conclusions Recent social changes such as declining birthrate, decline in public elementary schools, and increasing after-school activities may change parental attitudes toward children's walking to/from school, and subsequently, their mode of school travel over time. To maintain the high prevalence of walking to/from school in Japan, multidisciplinary approaches involving different stakeholders from education, public health, and urban planning are required to overcome sectionalism and support this behavior in the long term.